Analytical approach to solve the problem of aircraft passenger boarding during the coronavirus pandemic. (March 2021) - Schultz, Michael; Soolaki, Majid
Abstract: The corona pandemic significantly changes the processes of aircraft and passenger handling at the airport. In our contribution, we focus on the time-critical process of aircraft boarding, where regulations regarding physical distances between passengers will significantly increase boarding time. The passenger behavior is implemented in a field-validated stochastic cellular automata model, which is extended by a module to evaluate the transmission risk. We propose an improved boarding process by considering that most of the passengers are travel together and should be boarded and seated as a group. The NP-hard seat allocation of groups with minimized individual interactions between groups is solved with a genetic algorithm. Then, the improved seat allocation is used to derive an associated boarding sequence aiming at both short boarding times and low risk of virus transmission. Our results show that the consideration of groups will significantly contribute to a faster boarding (reduction of time by about 60%) and less transmission risk (reduced by 85%) compared to the standard random boarding procedures applied in the pandemic scenario. Highlights: COVID19 requirements complicate efficient passenger handling in the aircraft cabin. Physical distances between passengers extend the boarding time considerably. Need for improvement of seat allocation and passenger boarding sequences. Simulation, evaluation, optimization of boarding process for passenger groups. Consider passenger groups lead to faster boarding and less transmission risk.